2022
DOI: 10.1111/ajt.16829
|View full text |Cite
|
Sign up to set email alerts
|

Protecting kidney transplant recipients against SARS-CoV-2 infection: A third dose of vaccine is necessary now

Abstract: We have read the article written by Ison et al. 1 that has raised some issues we would like to discuss. COVID-19 breakthrough infection rates in vaccinated kidney transplant (KT) recipients much higher than in the general vaccinated population have been reported. 2 Furthermore, the severity remains markedly high. Although Ison et al. referred cases are rarely severe, other series, and among them, the largest cohort published so far, have reported 27% of very serious cases. 3 By August 2021, 843 KT recipients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…After review, 105 articles were excluded owing to being a review article, case report, preprint, incorrect patient population, or duplicate cohort or having no outcomes of interest. A total of 83 studies 9 , 10 , 11 , 12 , 13 , 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After review, 105 articles were excluded owing to being a review article, case report, preprint, incorrect patient population, or duplicate cohort or having no outcomes of interest. A total of 83 studies 9 , 10 , 11 , 12 , 13 , 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ...…”
Section: Resultsmentioning
confidence: 99%
“…The weighted mean (range) total seroconversion rate after 2 doses of mRNA COVID-19 vaccines was 44.9% (0%-79.1%) for antispike antibodies (53 studies 10 , 11 , 12 , 13 , 14 , 32 , 35 , 36 , 38 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 69 , 70 , 71 , 74 , 79 , 80 , 82 , 84 , 86 , 88 , 91 , 92 , 93 , 94 , 95 , 97 , 102 , 103 , 105 ) and 22.6% (0%-47.5%) for neutralizing antibodies (8 studies 12 , 49 , 62 , <...>…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It remains unclear how the humoral immune response as well as specific T-cell immunogenicity affect patients' actual protection from infection in the first place or from a severe course of disease, respectively. Villanego et al reported on a rate of 1.8% of completely vaccinated kidney transplant recipients developing a breakthrough infection and consecutively COVID-19 [6], whereas Aslam et al reported on an even lower rate of 4 out of 912 solid organ transplant recipients [7]. Malinis et al reported 0.65% of their fully vaccinated solid organ transplant recipients developed COVID-19 [8].…”
Section: Introductionmentioning
confidence: 99%